Inhibition of lipid peroxidation of Kiwicha (Amaranthus caudatus) hydrolyzed protein using Zebrafish Larvae and Embryos - Vilcacundo, Rubén (2018)
Amaranth protein concentrate (APC) was hydrolyzed under in vitro gastrointestinal conditions. APC proteins were partially degraded by pepsin at pHs 1.2, 2.0, and 3.2. During the intestinal phase (pepsin/pancreatin enzymes at pH 7.0), no polypeptide bands were observed in the gel, suggesting the susceptibility of amaranth proteins to the action of digestive enzymes. The potent in vitro inhibition of lipid peroxidation, shown by the gastric and intestinal digests, was confirmed in the zebrafish larvae, with a 72.86% reduction in oxidation of lipids in the presence of the gastric hydrolysate at pH 2.0, compared to a 95.72% reduction in the presence of the gastrointestinal digest. APC digests were capable of reducing reactive oxygen species (ROS) production in the zebrafish embryo model with a value of fluorescence of 52.5% for the gastric hydrolysate, and 48.4% for the intestinal hydrolysate.